1975
DOI: 10.1103/physrevlett.34.448
|View full text |Cite
|
Sign up to set email alerts
|

Electron Loss in Low-EnergyH+-H(high n)Merged-Beam Collisi

Abstract: We have measured the electron-loss cross section for collisions between protons and highly excited hydrogen atoms having principal quantum numbers in the nominal n band 44%n% 50. The cm. collision energy range was 0.4 eV^ pp^ 61 eV. Theoretical ionization-cross-section results are compared with the data and are then used to unfold from the data the approximate electron-transfer cross section. Classical scaling calculations are found to be in reasonable agreement with the unfolded data while quantal predictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Charge transfer cross sections involving electronically excited atoms are, however, known to be considerably larger. For example, Koch and Bayfield [19] studied the reaction H + +H(n = 47) and found an electron transfer cross section of the order of 10 6 -10 7Å2 compared with 30Å 2 for the ground state [20]. Thus, we conclude that the dominating process of formation of the atoms with hyper-thermal velocity is a charge transfer reaction in which electronically excited species are involved.…”
Section: Cross-sectionsmentioning
confidence: 83%
“…Charge transfer cross sections involving electronically excited atoms are, however, known to be considerably larger. For example, Koch and Bayfield [19] studied the reaction H + +H(n = 47) and found an electron transfer cross section of the order of 10 6 -10 7Å2 compared with 30Å 2 for the ground state [20]. Thus, we conclude that the dominating process of formation of the atoms with hyper-thermal velocity is a charge transfer reaction in which electronically excited species are involved.…”
Section: Cross-sectionsmentioning
confidence: 83%
“…We have shown that, for a good matching, one must add capture and ionization probabilities for the collision process to compare with the case of optical pulses. The electron loss defined can be measured experimentally, see for example [30]. Moreover, we have seen that the key parameter for the design of the pulses is energy, and not its duration.…”
Section: Discussionmentioning
confidence: 99%
“…A furnace target technique employing electric field ionization to detect excited collision products has been used by Bayfield et al [96] to determine cross-sections for capture into highly excited states of H in the process H'+H -+ H ( 1 3 < n < 2 8 ) + H + (10) Measured cross-sections in the range 7-60 keV for capture into all states between n = 13 and 28 attain a maximum value of about 7 x 10-'9cm2 at about 30keV. Roy et al [97] have shown that while the experimental cross-sections above 50 keV are much smaller than values predicted by the Oppenheimer-Brinkman-Kramers approximations, a satisfactory description is provided by calculations based on the approximations of Jackson and Schiff [98], Bassel and Gerjuoy [99] and Band [loo].…”
Section: Electron Capture Into Excited Statesmentioning
confidence: 99%